A Modified Delphi Process to Identify Process of Care Indicators for the Identification, Prevention and Management of Acute Kidney Injury after Major Surgery - Matthew T James; Neesh Pannu; Rebecca Barry; Divya Karsanji; Marcello Tonelli; Brenda R Hemmelgarn; Braden J Manns; Sean M Bagshaw; H Tom Stelfox; Elijah Dixon (Canadian Journal of Kidney Health and Disease, 2015)
Background: The outcomes of acute kidney injury (AKI) are well appreciated. However, valid indicators of high quality processes of care for AKI after major surgery are lacking. Objectives: To identify indicators of high quality processes of care related to AKI prevention, identification, and management after major surgery. Design: A three stage modified Delphi process. Setting: The study was conducted in Alberta, Canada using an online format. Participants: A panel of care providers from surgery, critical care, and nephrology. Measurements: The degree of validity of candidate indicators were rated by panelists on a 7-point Likert scale that ranged from “strongly disagree” to “strongly agree”. Methods: A focused literature review was performed to identify candidate indicators. A modified Delphi process, with three rounds, was used to obtain expert consensus on the validity of potential process of care quality indicators. Results: Thirty-three physicians participated (6 from surgery, 10 from critical care, and 17 from nephrology). A list of 58 potential process of care quality indicators for AKI after surgery was generated including 28 indicators from the initial literature review and 30 indicators suggested by panelists. Following the third round of questioning, 40 process of care indicators were identified with a high level of agreement for face validity; 16 of these reached high consensus among all panelists. Limitations: The consensus of panelists from Alberta, Canada may not be generalizable to other settings. The modified Delphi process did not focus on the feasibility of measuring these process indicators. Conclusions: These indicators can be used to measure and improve the quality of care for AKI after major surgery.